PENERAPAN METODE WATERFALL UNTUK PERANCANGAN SISTEM INFORMASI INVENTORY BERBASIS WEB (Studi Kasus: PT INOVASI ALCO PANEL) - Belief Populace Laia; Susanna Dwi Yulianti Kusuma (CV. Multi Kreasi Media, 2024)
Inovasi Alco Panel PT is a alderon distributor in South Tangerang, whose activities are For supplying need shop building every day. For fulfil need shop building then Inovasi Alco Panel PT does activity inventory of goods, in order to meet needs shop building can fulfilled. During this is an activity process the done with using Microsoft Excel so give rise to error in recording goods enter and goods go out. By Because that, writer try develop system inventory based web for give information availability goods with right time And accurate. Efficiency cost to items that will purchased for fulfil need will the real stuff needed by shop buildings, and reduce work And power Work. Making system inventory based this website done through stage design, implementation and testing. Planning done with using UML, implementation done using HTML, PHP, website And MySql whereas stage testing system done use method white box And black box Testing. Based on testing carried out can concluded that results from study This can overcome problem previously and in accordance with what was expected.